Selenium isotope systematics of mid-ocean-ridge basalts and implications for the long-term volatile and chalcophile record of the crust–mantle system - Yierpan, Aierken (Universität Tübingen, 2021)
Selenium is a chalcophile, moderately volatile and redox-sensitive element. The Se isotopic and elemental systematics of mantle-derived rocks and melts may therefore provide new approaches to study the terrestrial volatile origin and evolution as well as secular changes of redox conditions across the surface and mantle reservoirs. Selenium is significantly depleted in mantle samples (at ng/g levels), posing analytical challenges for Se isotopic studies of the igneous system. This study presents an analytical protocol suitable for precise and accurate determination of Se isotope and Se–Te abundances of igneous rocks. The Se–Te elemental systematics provide a petrogenetic context for interpreting Se isotope systematics. The new method was used to analyze a suite of basaltic glasses from the Pacific–Antarctic ridge (PAR) and the Mid-Atlantic ridge (MAR). The magmatic differentiation involving concurrent sulfide segregation results in significant chalcophile element fractionation but no measurable Se isotopic variation. Because of the demonstrated lack of Se isotopic fractionation between sulfides and silicate melt, the Se isotope systematics of MORB reflects a source signature. The southern MAR displays a significant source heterogeneity due to the localized interaction between the ridge and Shona and Discovery mantle plumes that incorporate recycled components.